Das Volk Israel und der Beginn seiner Gesellschaftsordnung: Ex 1–18 - Volgger, David (Liber Annuus, 2023)
Abstract The present study of Ex 1–18 confirms the distinction of the sources J, E and P(H) and the importance of the criteria for the textual formation of the three sources of Ex 1–18. This is based on a survey of Ex 3:16-18. With respect to the five criteria of Gen 12–50, another criterion is added that underlines the role of the prophetic leadership of Moses for the future social order of Israel. Based on these results, it appears reasonable to hypothesize a social milieu and epoch similar to the genesis of the three sources of Ex 1–18. Ultimately it would not be totally absurd to attribute Ex 1–18 – parallel to Gen 12–50 – to an “author” or a “group of authors”, if Ex 1–18 qualifies as a text written in a “compilation of sources” style.